Fundamental Concepts of Bioinformatics
Fundamental Concepts of Bioinformatics is the first textbook co-authored by a biologist and computer scientist that is specifically designed to make bioinformatics accessible to undergraduates and prepare them for more advanced work. Features Focus on fundamentally important algorithms at the core of bioinformatics. Easy-to-do "paper and pencil" calculations make fundamental algorithms unintimidating for biology students and accessible to students with limited experience in computer programming. Combined expertise (biology and computer science) of author team ensures an integrated approach and an appreciation for the biology and computer science tools and perspectives. Detailed solutions to selected text questions are provided in the back of the text so students can check their answers.